Effect of Thyroid-Stimulating Hormone Suppression on Muscle Function After Total Thyroidectomy in Patients With Thyroid Cancer - Lee, Jun Choul; Song, Byong-Sop; Kang, Young Mi; Kim, Yu-Ri; Kang, Yea Eun; Lee, Ju Hee; Shong, Minho; Yi, Hyon-Seung (Frontiers in Endocrinology, 2021)
Context: Thyroid-stimulating hormone (TSH) suppression is recommended to reduce tumor recurrence following surgery for differentiated thyroid cancer (DTC). However, prolonged subclinical hyperthyroidism caused by levothyroxine treatment has deleterious effects on various organs. Objective: To evaluate the relationships of TSH concentration with muscle mass, muscle strength, and physical performance related to sarcopenia in patients with DTC undergoing TSH suppression following surgery. Methods: We studied 134 patients of >60 years who were undergoing TSH suppression therapy following surgery for DTC. We evaluated muscle mass and muscle function-related parameters and diagnosed sarcopenia using the threshold for Asian people. Results: The participants were 68.3±7.2 years old and 36/134 (26.9%) were diagnosed with sarcopenia. They were allocated to high-TSH and low-TSH groups using a threshold concentration of 0.40 μU/mL, and grip strength was significantly lower in the low-TSH group. The data were further analyzed according to age and sex, and in the low-TSH group, male participants and those of <70 years were found to have significantly lower grip strength. Conclusions: Low-TSH concentrations is associated with low grip strength, and this is most pronounced in individuals of <70 years of age. Therefore, muscle function should be considered an adverse effect of TSH suppression in patients with DTC who undergo TSH suppression therapy, especially in men of <70 years.